Método automático para descoberta de funções de ordenação utilizando programação genética paralela em GPU - Coimbra, Andre Rodrigues (2014)
Ranking functions have a vital role in the performance of information retrieval systems ensuring that documents more related to the user’s search need – represented as a query – are shown in the top results, preventing the user from having to examine a range of documents that are not really relevant. Therefore, this work uses Genetic Programming (GP), an Evolutionary Computation technique, to find ranking functions automaticaly and systematicaly. Moreover, in this project the technique of GP was developed following a strategy that exploits parallelism through graphics processing units. Other known methods in the context of information retrieval as classification committees and the Lazy strategy were combined with the proposed approach – called Finch. These combinations were only feasible due to the GP nature and the use of parallelism. The experimental results with the Finch, regarding the ranking functions quality, surpassed the results of several strategies known in the literature. Considering the time performance, significant gains were also achieved. The solution developed exploiting the parallelism spends around twenty times less time than the solution using only the central processing unit.